2010
DOI: 10.1111/j.1365-2567.2010.03263.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of mumps virus‐specific memory B cells by transfer of peripheral blood mononuclear cells into immune‐deficient mice

Abstract: Summary Waning immunity to mumps after one or two doses of the measles, mumps and rubella (MMR) vaccine has been described. Using a human peripheral blood lymphocyte (PBL)–severe combined immunodeficiency (SCID) mouse model, MMR vaccine recipients with undetectable and high antibody titres against mumps were compared for the presence of circulating mumps‐specific memory B cells. Peripheral blood mononuclear cells (PBMC) from six donors (three subjects with undetectable and three with high antibody titres again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Hebeis et al demonstrated that the activation of virus-specific memory B-cells to secrete immunoglobulin G (Ig G) is autonomous of cognate or bystander T-cell help [ 68 ]. The role of virus-specific B-cell memory has been found in mumps virus [ 69 ], human influenza virus [ 70 ], rotavirus [ 71 , 72 ], and dengue virus [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hebeis et al demonstrated that the activation of virus-specific memory B-cells to secrete immunoglobulin G (Ig G) is autonomous of cognate or bystander T-cell help [ 68 ]. The role of virus-specific B-cell memory has been found in mumps virus [ 69 ], human influenza virus [ 70 ], rotavirus [ 71 , 72 ], and dengue virus [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“… 23,25 Finally, there is limited evidence that with the waning of antibodies, also memory B cells disappear and the long-term protection can not be guaranteed anymore. 26 These studies indicate that mumps vaccines appear to be less immunogenic than initially assumed. This implies that the primary immune response is able to eliminate mumps, but that the protection lasts less long than originally thought.…”
Section: Vaccine Failurementioning
confidence: 92%
“…Furthermore, the nature of the immune response to mumps seems to be inherently weak by some measures. Besides inducing typically low levels of neutralizing antibody, multiple reports indicate that the frequency of mumps-specific memory B-cells is also very low (35,58,59). It may be reasonable to try to improve the neutralizing antibody response by (re)directing it toward HN rather than NP, but other effects of antibodies, such as complement fixation, should not be overlooked (60,61).…”
Section: Discussionmentioning
confidence: 99%